The Relationship between the Implementation of Pregnancy Exercises and Leg Oedema in Pregnant Women in the Third Trimester at the Margasari Community Health Center - Siti Aisyah; Anik Sri Purwanti (Calory Journal Medical Laboratory Journal, 2025)
Background: Leg oedema is a common condition experienced by pregnant women, particularly during the third trimester, due to physiological changes such as increased blood volume and pressure on the lower extremities. This condition can cause discomfort, reduce mobility, and affect the quality of life of pregnant women. Pregnancy exercises are recommended as a non-pharmacological intervention to improve circulation, reduce fluid accumulation in the legs, and prevent or minimize oedema. Despite these recommendations, many pregnant women do not perform exercises regularly, and limited evidence is available regarding the effectiveness of structured pregnancy exercise programs in reducing leg oedema. Objective: This study aims to examine the relationship between the implementation of pregnancy exercises and the reduction of leg oedema in pregnant women in the third trimester at the Margasari Community Health Center. Methods: A quantitative pre-experimental study with a one-group pretest-posttest design was conducted. The sample consisted of 30 pregnant women in their third trimester experiencing leg oedema, selected using purposive sampling. The participants were guided to perform structured pregnancy exercises over a designated period, and the degree of leg oedema was assessed before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test to determine the effect of pregnancy exercises on leg oedema. Results: The Wilcoxon test indicated a statistically significant reduction in leg oedema following the implementation of pregnancy exercises, with a p-value of 0.000 (p < 0.05). This demonstrates that the intervention was effective in reducing fluid accumulation in the legs of pregnant women. Conclusion: Pregnancy exercises are effective in reducing leg oedema in women during the third trimester. Regular implementation of these exercises can improve maternal comfort, mobility, and overall quality of life